PELATIHAN DAUR ULANG SAMPAH PLASTIK BAGI MAHASISWA POLTEKKES KEMENKES TANJUNGKARANG (Poltekkes Kemenkes Bandung, 2023)
Community Service Activities (Pengabmas) have been carried out by the Poltekkes Kemenkes Tanjungkarang led by the Community Service Team, Department of Medical Laboratory Technology, to Community Community Service partners named the Green Community, which is a group of students from Poltekkes Kemenkes Tanjungkarang who are interested in environmental issues. Activities that have been carried out are in the form of training in the theory and practice of recycling plastic waste. The problem faced by community service partners is that they do not have the soft skills and hard skills and equipment in managing plastic waste recycling. The purpose of this community service activity is to train members of the Green Community to have soft skills and hard skills in managing plastic waste recycling. The method used in community service activities consists of three stages, where the first stage is preparation, the second is application and the third is activity evaluation. The results of this community service activity are that the Green community already has the equipment to recycle plastic waste and human resources that are able to recycle plastic waste.